Perencanaan Struktur Baja Gedung Parkir Universitas Hasyim Asy’ari Tebuireng Jombang - Safi Faozi; Amudi , Abdiyah; Sundari , Titin; Nugroho , Meriana Wahyu (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
Parking is a condition in which the driver/ rider stops and leaves his vehicle temporarily. For this reason, a comfortable and safe place is needed to leave their vehicle behind. To meet the parking needs, due to the increase in students and the arrangement of parking spaces, therefore it is planned to build a two-story parking building structure with a steel structure by using the Load and Resistance Factor Design (LRFD) method and to simplify the design of steel structures by using the analysis of the sap 2000 software. The result of this study is axial, moment. The truss model used is a gable frame and the steel material used is BJ37 with a WF profile while for the roof used is a zincalume structure. Those are planned to consider the safety of the effects of resistance and load, so that the design strength of each structural component cannot be less than the strength required, based on the combination loading. Based on the results of the research, it can be concluded that: the type of steel used is BJ 37, the gable beam of the truss used is WF 200.200.8.12 with pressure 132799.023 kg > 9524.06 kg, and the moment Mu ≤ ∅Mn gets load of 11328 kgm > 8527.34 kgm, and those meet the requirements needed. The column used is WF profile 300.300.10.15 with pressure 141891.12 kg > 22270.91 kg, and for the interaction equation between moment and axial is 0.83 < 1. The planned profiles above are then ready to be used.